A Daily Assessment Study of Smoking Cessation After a Head and Neck Cancer Diagnosis. Issue 11 (29th April 2022) - Borger, Tia; Shelton, Brent J; Valentino, Joseph; Ostroff, Jamie S; Cummings, Kenneth Michael; Studts, Jamie L; Carpenter, Matthew J; Burris, Jessica L
Abstract: Introduction: This intensive longitudinal study describes key events in the process of smoking cessation after a new head and neck cancer (HNC) diagnosis. Prior longitudinal studies show some cancer patients quit, while others continue to smoke, but details about the pattern in which these discrete outcomes arise are scarce. This study is meant to help rectify this gap in the literature. Aims and Methods: Participants were 42 HNC patients who reported current smoking at enrollment. Participants were recruited from an outpatient oncology clinic and completed a baseline questionnaire prior to begin a 30-day daily assessment. Results: Few participants (9.52%) achieved 30-day continuous abstinence from smoking. On average, participants reported 9.64 ± 11.93 total days of abstinence. Nearly, all (94.44%, n = 34) participants made at least one quit attempt, with an average of 16.94 ± 11.30 quit attempt days. Fewer participants were able to achieve a 24-hour quit attempt (52.78%, n = 19), with a corresponding average of 5.50 ± 8.69 24-hour days. The median time to first 24-hour quit attempt was 13 days after enrollment. Based on smoking behavioral patterns, participants were categorized into five groups, the most common being "persistent attempters, " which involved unsuccessful quit attempts throughout the study. Only 45% of participants ( n = 19) used evidence-based treatment, the most common being cessation medication. Conclusions: This intensive longitudinal study found that cancer diagnosis can spur a lot of efforts to quit smoking. Unfortunately, this study suggests that many quit attempts are short lived, possibly a result of an absence or insufficient use of evidence-based treatments. Implications: For adults who are current smokers at the time of cancer diagnosis, there is a high likelihood of persistent cigarette smoking and use of other tobacco products in the weeks and months after a cancer diagnosis. Furthermore, this study shows that while a lot of quit attempts may occur, few are successful, which may be partly attributable to the low use of evidence-based tobacco treatment. Future research with cancer patients should aim to identify predictors of quit attempts and abstinence as well as treatment utilization.